UMPSA and Futurise launch the Eastern Zone Dronecubator - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 27 August 2024 – For the first time, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Futurise have launched the Eastern Zone Dronecubator, an event held today at Block 1 Field, Faculty of Electrical and Electronics Engineering Technology (FTKEE), UMPSA.